Efficacy of neural mobilization and mid-carpal mobilization in the treatment of carpal tunnel syndrome = Skuteczność neuromobilizacji oraz mobilizacji stawu śródnadgarstkowego w leczeniu zespołu kanału nadgarstka - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Efficacy of neural mobilization and mid-carpal mobilization in the treatment of carpal tunnel syndrome = Skuteczność neuromobilizacji oraz mobilizacji stawu śródnadgarstkowego w leczeniu zespołu kanału nadgarstka. Journal of Education, Health and Sport. 2016;6(6):31-38. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54547 http://ojs.ukw.edu.pl/index.php/johs/article/view/3537 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. EFFICACY OF NEURAL MOBILIZATION AND MID-CARPAL MOBILIZATION IN THE TREATMENT OF CARPAL TUNNEL SYNDROME SKUTECZNOŚĆ NEUROMOBILIZACJI ORAZ MOBILIZACJI STAWU ŚRÓDNADGARSTKOWEGO W LECZENIU ZESPOŁU KANAŁU NADGARSTKA Janusz Kocjan Medical University of Silesia, Doctoral Studium of School of Medicine, Katowice, Poland Śląski Uniwersytet Medyczny, Studium Doktoranckie Wydziału Lekarskiego w Katowicach SUMMARY Introduction: Carpal Tunnel Syndrome (CTS) is a cause of functional impairment and chronic wrist pain of the hand. It results from compression of the median nerve as it passes through the carpal tunnel. Purpose: The purpose of this study was to determine the effect of a manual therapy techniques (median nerve neural mobilization and wrist traction) on measures of pain and hand function in individuals with carpal tunnel syndrome. Material and methods: 36 patients of ages between 35-50 years with clinical and electrodiagnostic evidence of carpal tunnel syndrome, as well as positive Phalen test participated in this study. Subjects were randomly assigned to one of the two physiotherapy intervention groups: Group I - only median nerve neuromobilization was applicated. Group II - median nerve neuromobilization technique with additionally performed mid-carpal distraction using manual therapy technique. Psychometric measures, Boston Carpal Tunnel Questionnaire (BCTQ), The Disabilities of the Arm, Shoulder and Hand (DASH) and Visual Analogue Scale (VAS) were used. Results: Both methods were very effective in the treatment of CTS. The results of the study demonstrated that a combination of neuromobilisation and mid-carpal distraction brought slightly greater gains in outcome measures: symptom severity, hand functional status and pain intensity, than neural mobilization single performed. although in some cases the differences were not statistically significant. Conclusions: It is concluded that the combination of these two techniques may be effective in the treatment of CTS, especially in second degree of CTS where patients have persistent numbness in the area supplied by the median nerve. However, further clinical studies are needed. Key words: carpal tunnel syndrome, neural mobilization, mid-carpal distraction.